k+hj=6

Simple and best practice solution for k+hj=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for k+hj=6 equation:


Simplifying
k + hj = 6

Reorder the terms:
hj + k = 6

Solving
hj + k = 6

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-1k' to each side of the equation.
hj + k + -1k = 6 + -1k

Combine like terms: k + -1k = 0
hj + 0 = 6 + -1k
hj = 6 + -1k

Divide each side by 'j'.
h = 6j-1 + -1j-1k

Simplifying
h = 6j-1 + -1j-1k

See similar equations:

| 3-6x=11x-8x | | -2y*-y=0 | | 6a^2-30a+24= | | 2.7x+2.8=19 | | -17=3+5 | | 9x-12+2x=11x+6 | | d-2.94=1.36 | | 2(3x+4)-3=6x+5 | | -5+9=21 | | 3m-10=24m-5 | | x/18+x/3 | | 8(y+6)+y=4(y+5)+2 | | 1/31/2x/3 | | -4(3x-4)+1=-12x+17 | | 5x+4=12+5x | | 2x-3+4x-8=13 | | 5*29= | | 7x-8y=64 | | 11*15= | | 2(x-4)(x-3)=x-13 | | 9x+6=9(x-3) | | X+4/3=x-8/5 | | X/4-3=-4 | | -8-3+6*2= | | 3z=14-29 | | 3(3m-2)+10=3(m-4)-3 | | 23x-7-14x+4=25x-4-16x+12 | | (5a-2)(7a+3)=0 | | 0.14(y-6)+0.04y=0.08y-0.1 | | 5-5(-5-7/-6)-13 | | -4(4x+1)=-52 | | 6x^2=10x+4 |

Equations solver categories